Health-related content in Australian television advertising - Baker, J.; Mullan, Barbara (Emerald Group Publishing, 2011)
Purpose – The purpose of this paper is to explore the proportions of health-related content in non-program time on Australian television, and how this relates to channel, product category, program genre and whether it is an advertisement or public service announcement (PSA). Design/methodology/approach – Australian prime time television was recorded across three commercial television stations in Sydney. Non-program content (NPC) was coded according to the channel, program genre, length of content and product advertised. In total, 44 hours of programming was recorded. Findings – Not surprisingly, significant differences were found in the percentage of health-related content between advertisements (22 percent) and PSAs (67 percent). Again unsurprisingly there was also a significant relationship between the product category and health-related content (x2 = 366.601, p = 0.000), but also between health-related content and program genre (x 2 = 20.594, p = 0.024), particularly situation comedies (31 percent) and sport (15 percent). No difference was found in the percentage of health-related content between the channels. Research limitations/implications – Differences existing in the amount of NPC across program genre suggest that viewers of programs with high rates of health-related content in advertising may have higher exposure to product dependant health information. Originality/value – Health information is examined in a general sample without focus on particular demographics or health topics and the role of program genre is investigated.